Strategic Risk: An Ordinal Approach - Collins, James M.; Ruefli, Timothy W. (Management Science, 1992)
Strategic management researchers have shown increasing awareness of the importance of the concept of risk at the strategic level. In recognition of this interest, this research adopts a commonly used conceptualization of risk and shows how this conceptualization leads to a new measure of risk, based upon the chance of loss of relative position within a set of firms. This framework is shown to be particularly appropriate for strategy research. Information contained in probability distributions describing the relative positions of sets of firms over time is shown to be partitionable on the basis of gain or loss in position as well as on firm identity, leading to the derivation of a new measure of strategic risk for an individual firm. This development also provides a hierarchical quantification of risk at the levels of the industry, group and individual firm. The ordinal risk measure is applied to both hypothetical data for illustration and to data on the U.S. airline industry.